A construção da imagem do Imperador Valente na obra de Sócrates Escolástico - Marques, José Renato da Silva (2009)
Socrates Scholasticus was one of the historians of the Church who lived and produced in the early fifth century AD. In his book, History of the Church, described the evolution of this institution as a chronological axis within the government of the Roman emperors. Referring to a background of creation of basilea, the sacred kingship RomanByzantine, which demanded specific attributes of the emperors, issued opinions on the performance of these. Wrote about some Emperors in a benevolent and praiseworthy way, but on others made severe criticism, as if they were not up to the job that, by divine delegation, exercised, including giving them the responsibility for natural disasters, invasions by barbarians and by attempts usurpation of the throne, from time to time ravaged the Roman Empire. With his comments helped to build a negative representation of the opponents of what he saw as orthodoxy, and to disparage the image of Valens, emperor of the eastern part of the Roman Empire between 364 and 378 A.D., since the emperor, Christian Arian sect heretic therefore, he pursued, sometimes with extreme violence, the Christian Nicene believers that prevailed as orthodox, which Socrates Scholasticus extremely supported.